(untitled) (Journal of Science Foundation, 2013)
An experiment was carried out at the Agronomy Field Laboratory, Bangladesh Agricultural University, Mymenshingh to study the effect of weeding regime on the weed infestation and crop performance on transplant aman rice. The treatments included 10 weeding regime - i) no weeding, ii) one hand weeding at 21 DAT, iii) two hand weeding at 21 and 42 DAT, iv) three hand weeding at 21, 42 and 63 DAT, v) Ronstar 25 EC @ 2.0 1ha-1 at pre-emergence, vi) 2, 4-D amine @ 1.84 1ha-1 at 42 DAT, vii) Ronstar 25 EC @ 2.0 1ha-1 at Pre-emergence + 2, 4-D amine @ 1.84 1ha-1 at 42 DAT, viii) Ronstar 25 EC @ 2.0 1ha-1 at Pre-emergence + one hand weeding at 42 DAT, ix) one hand weeding at 21 DAT + 2. 4-D amine @ 1.84 1ha-1 at 42 DAT and X) weed free. The experiment was laid out in a randomized complete block design with four replications. Weeding regime had significant effect on weed density and dry weight. Weed density and dry weight were significantly highest in the crop not weeded at all and lowest in Ronstar 25 EC @ 2.0 l ha -1 + one hand weeding . Plant height, total number of tillers hill-1, number of ear bearing tillers hill-1 , number of non ear bearing tillers hill-1 , number of grains panicle -1 ,number of sterile spike lets panicle -1, grain yield, straw yield, biological yield and harvest index were significantly affected by weeding regime. Ronstar 25 EC @ 2.0 1ha-1 + one hand weeding controlled the weeds to the greatest extent and produced the yield and yield attributes similar to those in weed free treatment. DOI: http://dx.doi.org/10.3329/jsf.v9i1-2.14645 J. Sci. Foundation, 9(1&2): 27-41, June-December 2011